Legal Construction in the Investigation Process from the Perspective of the Principle of Due Process of Law Analysis of the Relationship Between Authority, Ethics, and Police Reform (Case Study of Supreme Court Decision Number 1584 K/Pid/2015) - Indra Rahayu (Jurnal Indonesia Sosial Sains, 2026)
Indonesian criminal procedure law normatively guarantees human rights protection through the principle of due process of law. However, in practice, investigations frequently prioritize formal legality over substantive justice, rely heavily on investigators’ verbalization, and apply excessive pre-trial detention. This tendency is illustrated in Supreme Court Decision Number 1584 K/Pid/2015, where evidentiary construction was primarily based on testimonium de auditu—statements derived from investigators—rather than direct empirical evidence. This study aims to: (1) analyze the legal construction of criminal investigations from a due process perspective; (2) evaluate the relationship between investigator authority, discretion, and professional ethics in shaping evidence; and (3) formulate recommendations for institutional reform grounded in human rights protection. The research employs a qualitative normative-empirical approach through document analysis, examining statutory regulations, particularly the Criminal Code and human rights instruments, relevant jurisprudence, and legal scholarship on due process, discretion, and police ethics. The findings indicate that although investigations may formally comply with statutory provisions, substantively they deviate from due process principles. Evidence formation often depends on investigator narratives and post-incident testimony while neglecting objective proof, undermining material justice. Broad discretionary powers, weak internal oversight, and inconsistent professional ethics contribute to a gap between normative expectations (das sollen) and empirical reality (das sein). Consequently, structural reforms are required to strengthen evidentiary oversight, restrict pre-trial detention practices, and enforce stricter ethical standards to ensure fair investigations and safeguard suspects’ rights.